(untitled) (International Congress on Economics, Management and Business Studies, 2026)
Along with the growth and development of the body, proper nutrition is essential for healthy and physical and mental development. Deprivation of any nutrients that provide the body can cause significant damage to health, reduce resistance to external factors, and impair mental and physical performance. Nutrition is one of the leading factors affecting development about children’s health. The quantitative and qualitative indicators of nutrition determine the processes of physical development and functioning of the child’s body, as well as the adaptive environment and resistance to adverse factors in the school environment.